Indicators of acute bacterial meningitis in children at a rural Kenyan district hospital. - Berkley, J; Versteeg, A; Mwangi, I; Lowe, B; Newton, C (2004)
OBJECTIVE: Acute bacterial meningitis remains an important cause of death and neurologic sequelae in African children. The clinical features of meningitis are often nonspecific and in this setting may overlap with those of malaria. Early diagnosis and appropriate antibiotic treatment are perhaps the most important steps in management, but published data suggest that fewer than half of the cases of childhood meningitis are identified at first assessment in hospitals in this region. The objective of this study was to identify clinical indicators of acute bacterial meningitis by examining components of the World Health Organization Integrated Management of Childhood Illness (IMCI) referral criteria for meningitis (lethargy, unconsciousness, inability to feed, stiff neck, or seizures) and other symptoms and signs. METHODS: Kilifi District Hospital, serving approximately 200,000 people in a rural, malaria-endemic area of the Kenyan coast, was studied. A Kenya Medical Research Institute research center is located at the hospital. All pediatric admissions aged > or =60 days between June 2001 and July 2002 were eligible. RESULTS: A total of 91 (2.0%) of 4582 admissions had meningitis, including 77 (4.0%) of 1929 of those who met the IMCI referral criteria for meningitis at admission (sensitivity: 85%; specificity: 59%). Independent indicators of the presence of meningitis were a bulging fontanel, neck stiffness, cyanosis, impaired consciousness, partial seizures, and seizures outside the febrile convulsions age range. One or more of these indicators was present in 895 (19%) of admissions, 72 (8.0%) of whom had meningitis (sensitivity: 79%; specificity: 80%). Independent indicators of the absence of meningitis were the absence of a history of fever, a history of diarrhea, and a positive malaria slide. The area under the receiver operating characteristic curve for a set of simple screening rules based on the positive indicators identified was 0.88 (95% confidence interval: 0.85-0.92). CONCLUSIONS: The presence of > or =1 of a bulging fontanel, neck stiffness, cyanosis, impaired consciousness, partial seizures, and seizures outside the febrile convulsions age range is a clear indication for lumbar puncture and/or presumptive treatment. However, careful observation and reassessment may be the only practical way to identify one fifth of meningitis cases in this setting.